2010
DOI: 10.1111/j.1540-8159.2010.02952.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Zero‐Fluoroscopy Catheter Ablation of AVNRT: Early versus Late Experience

Abstract: Procedure time significantly shortens as a function of experience. After an adequate learning curve, the procedure can be performed in a very acceptable amount of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…The earliest study, by Bubolz et al [45], examined LCs in pediatric cardiac interventions and found the success rates to improve significantly, to as high as 93% with experience of <100 cases, whereas fluoroscopy times improved to 34 ± 27 min. Gist et al [46] explored the LC for zero-fluoroscopy approach of cryoablation to correct atrioventricular non-reentry tachycardia in 62 consecutive patients. Average procedure time declined by 42 min (p = 0.01) and recurrence rate reduced from 15% to 8% in later cohorts.…”
Section: Other Cardiovascular Surgery and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest study, by Bubolz et al [45], examined LCs in pediatric cardiac interventions and found the success rates to improve significantly, to as high as 93% with experience of <100 cases, whereas fluoroscopy times improved to 34 ± 27 min. Gist et al [46] explored the LC for zero-fluoroscopy approach of cryoablation to correct atrioventricular non-reentry tachycardia in 62 consecutive patients. Average procedure time declined by 42 min (p = 0.01) and recurrence rate reduced from 15% to 8% in later cohorts.…”
Section: Other Cardiovascular Surgery and Interventionsmentioning
confidence: 99%
“…A systematic review of LCs in cardiothoracic and vascular surgeries 209 [33][34][35][36][41][42][43][44]; and for ablation procedures, LCs were between 25 and 60 cases [45][46][47][48][49][50][51].…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Very few authors have focused on the complete elimination of fluoroscopy. To our knowledge, 4 studies reported zero-fluoroscopy AVNRT ablation in children in the great majority of cases [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in few reports the feasibility of fluoroless procedures in children and adolescents has been demonstrated [14][15][16][17] , with a similar success and complication rate compared to conventional standard ablation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…A zero‐fluoroscopy EPS using three‐dimensional (3‐D) electroanatomic mapping systems (3‐D EAM) is achievable for treatment of most arrhythmias, including AVNRT, but these navigation tools are related to higher costs and procedure times as compared to fluoroscopy guidance …”
Section: Introductionmentioning
confidence: 99%